Joint Assessment Mission Northern Sudan : Education Sector - World Bank (Washington, DC, 2013)
The objective of this report is to identify the main accomplishments and key barriers to educating all children in North Sudan by 2015 as per the Millennium Development Goals (MDG). This document assesses the current status of the formal education system in North Sudan and outlines priority actions, rehabilitation and transitional recovery needs as well as financing requirements for the period 2005 to 2010, which corresponds to the interim period of the Peace Agreement. (Unless otherwise specified, this report covers, and the word "Sudan" designates, all States in Sudan at the exclusion of Upper Nile, Equatoria and Bar el Ghazal states.) The report is based on information and documents collected during several country visits in 2004. It draws upon estimations of education indicators and performance trends in the education system reported in official statistics and studies conducted by various donor agencies. Economic data rely heavily on World Bank and IMF sources. Finally, this report focuses on basic education and training, which was considered to be the priority during the interim period. However, it also covers technical and vocational education, although in less detail than basic education.